-4(x+10)-6=7(x-2)-87

Simple and best practice solution for -4(x+10)-6=7(x-2)-87 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x+10)-6=7(x-2)-87 equation:



-4(x+10)-6=7(x-2)-87
We move all terms to the left:
-4(x+10)-6-(7(x-2)-87)=0
We multiply parentheses
-4x-(7(x-2)-87)-40-6=0
We calculate terms in parentheses: -(7(x-2)-87), so:
7(x-2)-87
We multiply parentheses
7x-14-87
We add all the numbers together, and all the variables
7x-101
Back to the equation:
-(7x-101)
We add all the numbers together, and all the variables
-4x-(7x-101)-46=0
We get rid of parentheses
-4x-7x+101-46=0
We add all the numbers together, and all the variables
-11x+55=0
We move all terms containing x to the left, all other terms to the right
-11x=-55
x=-55/-11
x=+5

See similar equations:

| 4,5×(x+3)=45 | | x+4*x=100 | | -11=3x-23 | | x+24=28+x | | 2x-2-6=0 | | 4(2x+5)=-35 | | 3m-7=2m+2 | | 4x/3+5/6=2/3 | | 4+3x=4x+2 | | (1+x)^34=1000000/5000 | | x+6=8x+10 | | (3x+88)+(x+6)+(2x-4)=180 | | 5x=2x+550 | | x*2,8=12,04 | | (3x+88)+(x+6)+(2x+4)=180 | | 1/2x+3=4x+5 | | 0,5x+3=4x+5 | | 2+5x=x+4 | | -4+8x-4x=4x-2x+x-2 | | 6)x+20+2x=56 | | 35-4x=2x+11 | | 2^-x+2x=0 | | 9)3+6x+2=29 | | z/5-7=6 | | 3x=2x+3= | | 5+5x=4x+2 | | x+5=0,5x+9 | | (13x+12)/3=5x+2 | | x+2=0,5x-1 | | 5x-32=3×-20 | | X=-3=q | | 10+x=0,5x+14 |

Equations solver categories